Two-years antibody responses following SARS-CoV-2 infection in humans: A study protocol - Arguni, Eggi; Dewi, Fatwa Sari Tetra; Fachiroh, Jajah; Paramita, Dewi Kartikawati; Lestari, Septi Kurnia; Wiratama, Bayu Satria; Susilaningrum, Annisa Ryan; Kharisma, Bara; Meisyarah, Yogi Hasna; Sari, Merlinda Permata; Farahdilla, Zakiya Ammalia; Siswanto, Siswanto; et al. (Public Library of Science, 2022)
The long-term antibody response to the novel SARS-CoV-2 in infected patients and their residential neighborhood remains unknown in Indonesia. This information will provide insights into the antibody kinetics over a relatively long period as well as transmission risk factors in the community. We aim to prospectively observe and determine the kinetics of the anti-SARS-CoV-2 antibody for 2 years after infection in relation to disease severity and to determine the risk and protective factors of SARS CoV-2 infections in the community. A cohort of RT-PCR confirmed SARS-CoV-2 patients (case) will be prospectively followed for 2 years and will be compared to a control population. The control group comprises SARS-CoV-2 non-infected people who live within a one-kilometer radius from the corresponding case (location matching). This study will recruit at least 165 patients and 495 controls. Demographics, community variables, behavioral characteristics, and relevant clinical data will be collected. Serum samples taken at various time points will be tested for IgM anti-Spike protein of SARS-CoV-2 and IgG anti-Spike RBD of SARS-CoV-2 by using Chemiluminescent Microparticle Immunoassay (CMIA) method. The Kaplan-Meier method will be used to calculate cumulative seroconversion rates, and their association with disease severity will be estimated by logistic regression. The risk and protective factors associated with the SARS-CoV-2 infection will be determined using conditional (matched) logistic regression and presented as an odds ratio and 95 confidence interval. Copyright: © 2022 Arguni et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.